Towards Net Zero in Poland: A Novel Approach to Power Grid Balance with Centralized Hydrogen Production Units - Dariusz Bradło; Witold Żukowski; Jan Porzuczek; Małgorzata Olek; Gabriela Berkowicz-Płatek (Energies)
The net zero emissions policy represents a crucial component of the global initiative to address climate change. The European Union has set a target of achieving net zero greenhouse gas emissions by 2050. This study assesses Poland’s feasibility of achieving net zero emissions. Currently, Poland relies on fossil fuels for approximately 71% of its electricity generation, with electricity accounting for only approximately 16% of the country’s total final energy consumption. Accordingly, the transition to net zero carbon emissions will necessitate significant modifications to the energy system, particularly in the industrial, transport, and heating sectors. As this is a long-term process, this article demonstrates how the development of renewable energy sources will progressively necessitate the utilisation of electrolysers in line with the ongoing industrial transformation. A new framework for the energy system up to 2060 is presented, with transition phases in 2030, 2040, and 2050. This study demonstrates that it is feasible to attain a sustainable, zero-emission, and stable energy system despite reliance on uncontrolled and weather-dependent energy sources. Preparing the electricity grid to transmit almost three times the current amount represents a significant challenge. The resulting simulation capacities, comprising 64 GW of onshore wind, 33 GW of offshore wind, 136 GW of photovoltaic, 10 GW of nuclear, and 22 GW of electrolysers, enable a positive net energy balance to be achieved under the weather conditions observed between 2015 and 2023. To guarantee system stability, electrolysers must operate within a centralised framework, functioning as centrally controlled dispatchable load units.